Implementasi Metode Role Playing Dalam Pembelajaran Akidah Akhlak - Cahyani, Elvita Indah; Wulandari, Putri; Munawir, Munawir (LP2M Universitas Islam Ahmad Dahlan, 2023)
The purpose of this study is to analyse in depth the role playing method when studying Aqidah Akhlak in class. The urgency of this research is due to students' low knowledge of learning moral beliefs. This happens due to a lack of encouragement and motivation to learn, a lack of teacher attention to the choice of learning methods used when teaching. This research uses qualitative methods and a descriptive approach, data sources obtained from library research, data collection techniques using literature reviews, and documentation then researchers' data analysis techniques use descriptive methods. Through this method, obtained results that by applying the role playing method can foster student motivation and improve learning outcomes as proven in previous studies; in pre-cycle to cycle I there was an increase of 20%, meanwhile in cycle II it exceeded the target with a percentage of 83.7%. So it can be said that the role playing method is very efficient and effective for use in religious learning, especially in the subject of Aqidah Morals.